Tolerância de espécies florestais arbóreas e fungos ectomicorrízicos ao cobre - Silva, Rodrigo Ferreira da (2007)
The contamination of soil for copper had refusal contribute to plants establishment in mining and vineyards areas of South Brazil. Mycorrhyzal forestry species could be one alternative to viable the development of plants in contaminated areas for heavy metals. The work was developed at Soil Department and Botanical Garden, in Federal University of Santa Maria; FEPAGRO- FLORESATA, Santa Maria-RS and Camaquã Mines, RS. Firstly, it was evaluated the mycorrhizal occurrence in forestry species like Luehea divricata Mart. et Zucc., Parapiptadenia rigida (Benth) Brenan, Peltophorum dubium (Sprengel) Tauber., Cedrela fissilis Vell., Eugenia involucrata Dc., Fícus puschnathiana (Miq.) Miq., Apuleia Ieiocarpa (J. Vogel) J.F. Macbr., Inga marginata Willd., Tabebuia Alba (Cham.) Sandwith, Tabebuia heptaphylla (Vell.) Toledo, Enterolobium contortisiliquum (Vell.) Morong., Tipuana tipu (Benth.) O. Kuntze and Phytolacca dioica L. Roots and soil sampling were performed at Botanical Garden of Federal University of Santa Maria and in native forest on Boca do Monte, district of Santa Maria, RS. No one of studied species had found ectomycorrhizal association in natural environment conditions. Roots of Luehea divricata, Parapiptadenia rigida, Peltophorum dubium, Cedrela fissilis, Fícus puschnathiana, Ingá marginata, Tabebuia Alba, Tabebuia heptaphylla, Enterolobium contortisiliquum, Tipuana tipu and Phytolacca dioica had arbuscular mycorrhizal. An experiment in liquid and solid culture medium was conducted to select copper tolerant ectomycorrhizal fungi. The fungi tested in solid medium were: Pisolitus microcarpus UFSC-Pt116, Suillus sp. UFSM RA2.8, Suillus sp. UFSM RA118, Scleroderma sp. UFSM SC3.6 and Scleroderma sp. UFSC-Sc124. In liquid culture medium were tested the species: Pisolitus microcarpus UFSC-Pt116, Pisolitus tinctorius UFSC-Pt24, Scleroderma sp. UFSC-Sc124, UFSM MC and UFSM RA2.8. The fungi UFSC-Pt116 showed copper tolerance and produced high amount of fungi mycelium. Latter, it was characterized ectomycorrizal on Parapiptadenia rigida, Peltophorum dubium, Apuleia Ieiocarpa and Enterolobium contortisiliquum seedlings in vitro conditions, cultivated and previously inoculated with the ectomycorrhizal fungi UFSC-Pt116. Seedlings of Parapiptadenia rigida, Peltophorum dubium and Enterolobium contortisiliquum was formed association with UFSC Pt 116. The region of transcribed internal space was studied and evaluated the differences in sequencing polymorphism of this region of isolated UFSC-Pt116, it was compared to other ectomycorrhizal fungi like Pisolithus, Sclerodrema, Rhizopogon and Suillus available in the GenBank data. It was confirmed the morphological identification of the isolates as belonging to the genus Pisolithus. However, with molecular results did not confirm the species of this fungus. The second part, it was evaluated the tolerance to copper for forestry species like Parapiptadenia rigida, Peltophorum dubium, Cedrela fissilis and Enterolobium contortisiliquum. Seedlings of Cedrela fissilis was evidenced copper accumulation on leaves, stem and roots. Seedlings of Enterolobium contortisiliquum was accumulated copper on roots, but the metal was not translocated to stem and leaves. It is possible to consider Parapiptadenia rigida as a cooper excluding plant. Peltophorum dubium, Parapiptadenia rigida and Enterolobium contortisiliquum was showed high tolerance to contaminated soil with copper. The thirdly part, it was evaluated the behavior Peltophorum dubium seedlings inoculated with the UFSC Pt 116 ectomycorrhizal fungi in soil with high copper concentrations. The increasing of copper doses was reduced root length, specific root surface area, height and stem diameter of Peltophorum plants. Seedlings of inoculated Peltophorum were showed less copper concentration on tissues and reduced copper absorption on more elevated doses. It was concluded that isolates UFSC-Pt116, UFSC-Pt24 and UFSC-SC124 were efficient on mycelium production in medium with high copper amounts. The isolated UFSC-Pt116 was not efficient to promote Peltophorum growth in soil with high copper concentration, but this isolated was reduced the copper absorption for plant.